Ketamine stereoselectively inhibits spontaneous Ca2+-oscillations in cultured hippocampal neurons. - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Martin, Eike O.; Fink, Rainer; Graf, Bernhard M. (Anesthesia and Analgesia, 2005)
Spontaneous Ca2+-oscillations are a result of periodic increases and decreases of cytosolic Ca2+. In neurons, they are thought to possess integrative properties because amplitude and frequency influence axon outgrowth, neuronal growth cone migration, and long distant wiring within the developing cortex. Ketamine stereoisomers differ in their affinities for the N-methyl-D-aspartic acid receptor and analgesic and anesthetic effects. Using a dual-excitation Ca2+ ratiometric fluorescence technique with the Ca2+-sensitive dye fura-2 AM, we detected spontaneous Ca2+-oscillations in neurons of hippocampal cell cultures. Spontaneous Ca2+-oscillations development is dependent on external Ca2+, and their amplitude and frequency increased in Mg2+-free solution. Ca2+-oscillations are glutamate dependent because blocking of the N-methyl-D-aspartic acid, alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic, or kainate receptor resulted in a complete disruption of the oscillations. The ketamine stereoisomers dose-dependently and reversibly suppressed the amplitude and frequency of the spontaneous Ca2+-oscillations. This effect was highly stereoselective with the S+ isomer being nearly four times more potent than the R(-) enantiomer. These results correlate well with the clinical anesthetic and analgesic potency of the stereoisomers and therefore our experimental approach might represent a model system to study mechanisms of anesthetic action on Ca2+-dependent integration of neuronal information.